1961
DOI: 10.1136/jcp.14.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the blood lipids and lipoproteins in thalassaemia and sickle cell anaemia

Abstract: Previous studies from this clinic and from other centres (Allamanis, 1955; Panizon, 1957) have demonstrated disturbances in the electrophoretic pattern of the blood proteins in thalassaemia major and sickle cell anaemia consisting of a slight to moderate fall of the albumin fraction, a raised y globulin fraction, and abnormal liver function tests. The relative value of these findings led us to study the lipid metabolism (Ackermann, Toro, and Kountz, 1954; Rafstedt, 1955; Salt and Wolff, 1957) of chronic hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0
2

Year Published

1967
1967
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
2
7
0
2
Order By: Relevance
“…In fact it seems that the value of serum total cholesterol in anaemias of various aetiology is re lated to the haematocrit [29]. On the other hand, the value of serum total cholesterol does not influence the survival time of erythrocytes, their cho lesterol content, nor their osmotic fragility [29], Our data regarding cholesterol and total phospholipids are in agree ment with the above observations [5].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In fact it seems that the value of serum total cholesterol in anaemias of various aetiology is re lated to the haematocrit [29]. On the other hand, the value of serum total cholesterol does not influence the survival time of erythrocytes, their cho lesterol content, nor their osmotic fragility [29], Our data regarding cholesterol and total phospholipids are in agree ment with the above observations [5].…”
Section: Discussionsupporting
confidence: 81%
“…Panizon [22] found a decrease in a-lipoproteins in patients affected by Cooley's disease; Choremis et al [5] confirmed this finding and also found an increase of /5-lipoproteins and a decrease of total lipids, choles terol and phospholipids. Both authors attributed these observations to the frequent hepatic damage found in such patients.…”
Section: Discussionsupporting
confidence: 62%
“…Hepatic dysfunction due to sequestration of liver tissue by sickled red cells is well known. This is evidenced by hypoproteinaemia; hypoalbuminaemia; altered albumin/ globulin ratio [1,2]; altered lipid metabolism with associated hypolipidaemia, and de creased E/C ratio [2-5], Relatively little is known about the state of liver function in sickle cell trait carriers [2].In view of the possible marginal bio chemical lesions in the liver of sickle cell trait carriers, we present here the changes in blood haemoglobin, serum total protein, al bumin, total cholesterol and serum trans aminases (glutamic-oxaloacetic acid, SGOT, and glutamic-pyruvic, SGPT) in a group of healthy subjects carrying sickle cell gene (traits and homozygotes) compared with those having haemoglobin A. …”
mentioning
confidence: 99%
“…Our findings in the schoolboys with G6PD deficiency are not statistically different from those in the control group. Choremis et al (1961), studying the blood lipids and lipoproteins in thalassaemia and sickle-cell anaemia, reported lower serum lipids and a characteristic lipoprotein distribution on paper electrophoresis. We cannot, however, compare our results with their findings, as we were not dealing with patients with the disease, and because their studies were done in both sexes, in a much wider age range, most probably with much lower Hb levels (the Hb levels of their patients are not mentioned).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of serum cholesterol in different ethnic groups has shown important differences (Adlersberg and Schaefer, 1959), but it cannot yet be decided if these differences are caused by genetic factors, by diet, or by other environmental influences (Adlersberg, Schaefer, Steinberg, and Wang, 1956). Choremis, Kyriakides, and Papadakis (1961), studying children with Cooley's anaemia and sicklecell anaemia, reported decreased values of serum lipids as determined by chemical analysis. Westerman, Pierce, and Jensen (1964) also found plasma total lipid, total phospholipid, and total cholesterol concentrations to be significantly lower in patients with sickle-cell anaemia than in a group of normal subjects.…”
mentioning
confidence: 99%